Partial test of social marketing strategy on smallholder farmers flood preparedness behavior in East Coast Malaysia - Muhammad Gazali, Umar; Man, Norsida; Abdullah, Amin Mahir; Mohd Nawi, Nolila; Abd. Latif, Ismail (International Organization Of Scientific Research (IOSR), 2018)
Flood is the most frequent among natural disasters in East Coast Malaysia. It causes loss of lives destruction of farm crops, livestock and properties. These affect productivity, income and livelihood. For flood impact to be reduced, disaster risk re\duction measures are highly imperative. Disaster risk reduction measures are divided in to post-disaster and pre-disaster. Despite the fact that the latter proved to be more effective, government and individual semphasized less on it. Farmers mostly rely on government for rehabilitations after disasters. Although disaster cannot be prevented but its effect could be reduced through preparedness. Preparedness decisions are based on past experience in the area which often fail. Attitude and behavior towards preparedness is low. How could this this be changed? Behavioral theories such as Social Marketing Theory and Theory of Planned behavior have the capacity to influence behavior. The objective of this study is to partially test social marketing strategy on farmers’ preparedness behavior. A multistage sampling technique was employed to select four hundred and twenty two respondents from Pahang, Kelantan and Terengganu. Structural Equation Model analysis was conducted. The overall hypothesis was tested on individual path regression weights. The results revealed that promotion mix was the strongest predictor of flood preparedness behavior. Intention was also found to mediate the relationship between attitude and flood preparedness behavior. In conclusion, the study found that the hypothesized model that social marketing strategy significantly affect farmers flood preparedness behavior were supported. It is recommended that government should include social marketing strategies in its design of policies and programs on flood preparedness in the future.